2021
DOI: 10.1021/acs.langmuir.1c00858
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Poly(l-lactic acid) Membranes with Fish-Scale Hierarchical Microstructures and Their Potential Application in Oil–Water Separation

Abstract: In this work, superhydrophobic poly(L-lactic acid) (PLLA) hierarchical membranes exhibiting excellent oil-removal performance, which is of great importance in curbing the oil-pollution environment, were fabricated by a simple solvent-evaporation-induced precipitation method. PLLA membranes with hierarchical micro/ nanostructures (fish scales, fibrous sheets, and petal-like morphology) can be conveniently prepared by adjusting the preparation parameters including PLLA concentration, precipitation temperature, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…Owing to the density difference of solvent (chloroform, 1.484 g/cm 3 ) and non-solvent (ethanol, 0.789 g/cm 3 ), an interface layer was produced and the PLLA chains migrated along the concentration gradient; furthermore, free energy was reduced, finally leading to liquid−liquid phase separation. 28 In accordance to our previous articles, 34,35 during the phase separation process, PLLA solution is able to be separated into PLLA-rich and PLLA-poor phases. The PLLA-rich phase consists of PLLA and solvent and acts as the continuous phase, eventually forming fibrous networks.…”
Section: ■ Results and Discussionsupporting
confidence: 78%
“…Owing to the density difference of solvent (chloroform, 1.484 g/cm 3 ) and non-solvent (ethanol, 0.789 g/cm 3 ), an interface layer was produced and the PLLA chains migrated along the concentration gradient; furthermore, free energy was reduced, finally leading to liquid−liquid phase separation. 28 In accordance to our previous articles, 34,35 during the phase separation process, PLLA solution is able to be separated into PLLA-rich and PLLA-poor phases. The PLLA-rich phase consists of PLLA and solvent and acts as the continuous phase, eventually forming fibrous networks.…”
Section: ■ Results and Discussionsupporting
confidence: 78%
“…Superhydrophobic surfaces with a water contact angle (WCA) larger than 150°and sliding hysteresis angle (SHA) less than 10°, play a key role in many fields due to their extremely water repellent properties such as self-cleaning, [1][2][3][4][5] anti-icing, [6][7][8] metal anti-corrosion, 9 fog harvesting, 10 marine drag reduction 11 and oil-water separation. [12][13][14][15][16][17][18][19] Through the study of the lotus leaf surface which can make raindrops roll and bounce to remove contaminants, it is found that micro-nano "papillae" structures and the waxy substance covering the surface are the main reasons for this "self-cleaning" phenomenon. 20 Furthermore, rough structure and chemical composition are highly correlated with hydrophobicity from the classical Wenzel 21 and Cassie-Baxter models.…”
Section: Introductionmentioning
confidence: 99%
“… 47 , 48 The addition of nanosilica particles into the PLA polymer solution was tried, and water θ increased up to 167° for the final composite PLA film, giving a porous network structure after phase inversion. 49 , 50 Alternatively, the addition of poly- d -lactic acid (PDLA) polymer to the poly( l -lactic acid) (PLLA) polymer resulted in the formation of stereo-complexed crystals, giving a morphology that was very different from the porous structure of pure PLLA with a water θ up to 155° and having good anti-icing properties. 51 A SH-PLA foam to be used for oil–water separation was prepared after dissolving PLA in dioxane solvent and applying freeze-drying and skin peeling.…”
Section: Introductionmentioning
confidence: 99%
“…The same group prepared SH-PLA surfaces using solvent/ternary non-solvent-coated PLA films to control the adhesion of water. , Only chloroform was used as the solvent, and n -butyl acetate, absolute ethanol, and n -butyl alcohol were mixed together at equal volume ratios to be used as the ternary non-solvent. The obtained polymer solution was coated onto another flat PLA substrate to form an SH-PLA layer and used to form microdroplet arrays in biochips for a no-mass-loss transport process. , The addition of nanosilica particles into the PLA polymer solution was tried, and water θ increased up to 167° for the final composite PLA film, giving a porous network structure after phase inversion. , Alternatively, the addition of poly- d -lactic acid (PDLA) polymer to the poly­( l -lactic acid) (PLLA) polymer resulted in the formation of stereo-complexed crystals, giving a morphology that was very different from the porous structure of pure PLLA with a water θ up to 155° and having good anti-icing properties . A SH-PLA foam to be used for oil–water separation was prepared after dissolving PLA in dioxane solvent and applying freeze-drying and skin peeling.…”
Section: Introductionmentioning
confidence: 99%